Contemporary Issues in Sustainable Finance: Exploring Performance, Impact Measurement and Financial Inclusion - La Torre, Mario; Leo, Sabrina (Springer International Publishing, 2023)
1. Introduction -- Section 1 -- 2. How to scale impact investments? Evaluating the application of the Synthetic Control Method in impact measurement -- 3. Impact investments measurement: bridging research and practice -- 4. ESG Ratings, scores, and opinions. The state of the art in literature -- Section 2 -- 5. Corporate financial performance and ESG performance: which one leads European banks? -- 6. Is performance the key issue in SRI funds? Conclusion and lessons learned from three decades of studies -- 7. The financial side of the Social Impact Bond: the determinants of the returns -- 8. Catastrophe Bonds: A Mitigation Opportunity In Turmoil Period -- Section 3 -- 9. Collaboration or Community? The Impact of the Institutional Forces in Promoting Social Crowdfunding -- 10. Financial Inclusion and the Gender Gap across Islamic and non-Islamic Countries.
Keywords: Aufsatzsammlung